The making of a new past for a "new" South Africa :the commemoration of Robben Island - Rioufol, Veronique (Department of Political Studies, 2024)
This study examines the interplay between the constitution of a new vision for society and new identity in post-apartheid South Africa and the corollary reshaping of the public representation of the past. In the first part, I construct a theoretical framework by combining theoretical literature on collective representations, collective memory, historiography, social identity and nationhood. Opting for constructivist theories and adopting a discourse analysis approach to collective representations of the past and to social identity, I analyse these phenomena as social constructs which are socially modelled and therefore reflect the broader social factors and processes (values, institutions, discursive practices and power configurations) which shape them. I further highlight that the representation of the past is at the core of the formation and evolution of identity. Specifically, there is an organic link between the formation of national identity and the shaping of the public representation of the "national past", the latter seeking to support and portray the image of national cohesion, hence providing an homogenising and often authoritative representation of the past. In the second part, I draw on this framework to examine the case of post-apartheid South Africa where the changeover has brought about a new project of society striving for democratisation, reconciliation, national unity and break with the past. A new identity narrative is thus taking shape which materialises and fosters these values and goals. As a corollary, a new public representation of the past has emerged -more or less self-consciously promoted- in congruence with the new identity narrative. The interplay between national identity narrative and public representation of the past is all the more significant in South Africa as dealing with the past has been regarded as a cornerstone of the reconstruction and reconciliation of the society. In this context, reshaping the representation of the past aims at promoting a redressed and shared representation and thereby fostering democratisation and national cohesion; at the same time, this entails the construction of a presentist and authoritative representation of the past. Above all, the reshaping of the past provides a conciliatory narrative which includes the representation of the diverse cultures and histories, fosters consensus about the past, tames painful and divisive memories, furthers reconciliation, recasts existing identities and celebrates the advent of the "new" South Africa . In the third part, I examine the specific case of the foremost commemoration of the "new" South Africa, that of Robben Island, in the light of the aforementioned theoretical framework and macro level analyses developed in Parts One and Two. For this case-study, I rely on academic sources, press and archives materials and qualitative field studies on Robben Island (observation of tourist visits and of the 1998 Youth Day commemoration, participation in a consultative symposium on the organisation and future of the museum, interview with the director, etc.). I then conclude that the commemoration of Robben Island -and its institutionalisation in the form of the Robben Island Museum- at once shapes and exemplifies the dynamics highlighted at the South African level.